Effects of feeding diets with different protein levels on preference and some blood parameters in dogs - Fatma İnal; Mustafa Selçuk Alataş; Oğuzhan Kahraman; Şeref İnal; Mustafa Uludağ; Emel Gürbüz; Esad Sami Polat (Eurasian Journal of Veterinary Sciences)
Aim: This study aimed to establish the effect of different dietary protein levels on certain blood parameters and food preference of dogs. Materials and Methods: A sample of 30 neutered, adult male dogs, with live weights of approximately 15-30 kg. Twenty-eight of dogs were fed four manufactured diets that respectively contained 18%, 21%, 25%, and 28% crude protein in dry matter for a period of one month. Blood samples were taken at the beginning and at the end of the study. Results: The blood urea nitrogen levels were found to be significantly affected by the protein level in the diet, however, creatinine, total protein, albumin, and phosphorus levels were not found to be directly affected by dietary protein. It was determined that dogs prefer food with higher protein content in the preference test conducted with thirty dogs. Conclusion: There were no adverse effects on the blood parameters of the different protein levels. The effects of high protein foods on kidney function should be monitored using different methods.